2020
DOI: 10.4000/travailemploi.10006
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Intensity and Hardships of Hospital Work in France (1998-2013)

Abstract: Direction de l'animation de la recherche, des études et des statistiques (Dares) 2020 Special Edition -Travail et Emploi -5 Changes in the Intensity and Hardships of Hospital Work in France (1998-2013) *

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
1
0
1
Order By: Relevance
“…It is particularly challenging to consistently demonstrate excellent interpersonal skills in this context. Research conducted in French hospitals has revealed frequent instances of tense communication, interpersonal con icts and dysfunctional relationships, which have detrimental effects on performance, supervision of trainees, quality of care, and potentially contribute to burnout (Benallah & Domin, 2020). Communication is recognized as a cornerstone of healthcare, applicable to all aspects of medical practice (King & Hoppe, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…It is particularly challenging to consistently demonstrate excellent interpersonal skills in this context. Research conducted in French hospitals has revealed frequent instances of tense communication, interpersonal con icts and dysfunctional relationships, which have detrimental effects on performance, supervision of trainees, quality of care, and potentially contribute to burnout (Benallah & Domin, 2020). Communication is recognized as a cornerstone of healthcare, applicable to all aspects of medical practice (King & Hoppe, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Pour un même constat, plusieurs explications peuvent être avancées. Les horaires décalés, les routines laborieuses, la pénibilité du travail de soin (Martin & Gadbois, 2004) (Alcaraz-Mor et al, 2019 sont souvent présentés comme les principales causes du désenchantement (Benallah & Domin, 2020). La carrière hospitalière étant traditionnellement figée, encadrée par la loi, les évolutions professionnelles et salariales tendent à être lentes et l'ascension dans une échelle hiérarchique est graduelle.…”
Section: Introductionunclassified